PENGEMBANGAN BAHAN AJAR FLASH BOOK SEJARAH PERADABAN INDONESIA MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD - Mahendra, Hatma Heris (Universitas Negeri Surabaya, 2019)
ABSTRACTThis study aims to (1) describe the feasibility of Indonesian history of civilization flash book as a developed teaching material, (2) describe the effectiveness of Indonesian history of civilization flash book as a teaching material to improve student learning outcomes. This is a development research with a 4-D design. This study consists of four stages including defining, designing, development, and disseminate. This research was conducted in SDN Medokan Ayu I/270 Surabaya, with the students from V A class as the control group and the students from V B class as the experimental group for 2015/2016 academic year. The feasibility assessment on the result of the development of the flash book as a teaching material was carried by a material and media experts as the validators. Hypothesis testing was done using a written test in the form of pre-test and post-test. The data obtained included the validator assessment of the material indicating the percentage of the assessment results by 93.75%, which was categorized as excellent, and the validator assessment of the media indicating the percentage of the assessment results by 91.67%, which was categorized as very good. Based on the assessment from the expert validator, the developed teaching material which in this case is the flash book, was declared feasible. Meanwhile, the hypothesis testing analyzed using T-test showed that the learning outcomes of the students in the experimental group is higher than the learning outcomes of the students in the control group. This is indicated by the value of tcount (3979) > ttable (1673). Therefore, the use of flash book as a teaching material affected the students' learning outcomes. Based on the analysis, it can be concluded that the Indonesian history of civilization flash book was feasible as a teaching material, and it effectively improved the learning outcomes of fifth grade students of primary school.imary school. Keywords: Teaching Material, Flash Book, Learning Outcmes. ABSTRAK Penelitian ini bertujuan untuk (1) mendeskripsikan kelayakan bahan ajar flash book sejarah peradaban Indonesia yang telah dikembangkan, (2) mendeskripsikan efektivitas bahan ajar flash book sejarah peradaban Indonesia dalam meningkatkan hasil belajar siswa. Penelitian ini merupakan jenis penelitian pengembangan dengan desain penelitian 4-D. Penelitian ini meliputi empat tahap yaitu pendefinisian, perancangan, pengembangan, dan penyebaran. Penelitian ini dilaksanakan di SDN Medokan Ayu I/270 Surabaya, dengan subjek penelitian adalah siswa kelas V A SDN Medokan Ayu I/270 Surabaya sebagai kelas kontrol dan V B SDN Medokan Ayu I/270 Surabaya sebagai kelas eksperimen tahun pelajaran 2015/2016. Penilaian kelayakan pada hasil pengembangan bahan ajar flash book dilaksanakan oleh validator ahli materi dan validato ahli media. Pengujian hipotesis dilakukan dengan menggunakan tes tulis berupa pre test dan post test. Data hasil penelitian yang diperoleh sebagai berikut penilaian dari validator ahli materi yang menunjukkan presentase hasil penilaian sebesar 93,75% yang tergolong sangat baik dan penilaian dari validator ahli media yang menunjukkan presentase sebesar 91,67% yang tergolong sangat baik. Berdasarkan penilaian dari validator ahli tersebut bahan ajar flash book yang dikembangkan dinyatakan layak. Sedangkan untuk pengujian hipotesis yang dianalisa dengan uji t menunjukkan bahwa hasil belajar siswa pada kelas eksperimen lebih tinggi dibandingkan hasil belajar siswa pada kelas kontrol. Hal ini ditunjukkan dengan nilai thitung (3.979) > ttabel (1.673). Jadi, penggunaan bahan ajar flash book berpengaruh terhadap hasil belajar siswa.Berdasarkan hasil analisis data, dapat disimpulkan bahwa bahan ajar flash book sejarah peradaban Indonesia layak dan efektif meningkatkan hasil belajar siswa kelas V sekolah dasar. Kata Kunci: Bahan Ajar, Flash Book, Hasil Belajar.